(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the effect of feeding with own mother’s milk on the incidence of bronchopulmonary dysplasia (BPD) and other preterm morbidities in very low birth weight (VLBW) infants.Materials and Methods: VLBW infants followed in our unit were divided into three groups according to their predominantly feeding type such as own mother’s milk group (MM), preterm formula group (PF) and mix fed group (MxF) in the first postnatal month. Groups were compared regarding demographic and clinical features including BDP. Results: The mean birth week of 117 VLBW infants was 29.3 ± 2.1 weeks and the mean birth weight was 1115 ± 265 g. Seventy seven infants were in the MM group, 17 infants were in the PF group and 23 infants were in the MxF group. There was a significant decrease in BPD incidence in the MM group compared to infants in the PM group (p=0.03). The frequency of necrotizing enterocolitis, late-onset sepsis and severe intraventricular hemorrhage (IVH) were found to decrease in the MM group when compared with other infants.Conclusion: The incidence of BPD decreases in VLBW infants fed with their own mother’s milk compared to VLBW infants fed with formula. Also besides feeding with mother’s milk may contribute to a decrease in the frequency of severe IVH.Keywords: Breastfeeding; bronchopulmonary dysplasia; intracranial hemorrhages; mother’s milk; newborn